Contramolde medular em conexão orgânica com fragmento lenhoso de Retemedulloxylon da Formação Rio Bonito (Eopermiano da Bacia do Paraná), Santa Catarina, Brasil - MERLOTTI, SHEILA (Pesquisas em Geociências, 1999)
This work records the occurrence of a pith cast connected with wood fragment in a fossil assemblage proceeding from Pouso Redondo County, Santa Catarina State, Brazil, in sediments from the Rio Bonito Formation, Eopermian of the Paraná Basin. The pith cast, cylindrical, is highly siliceous and unprovided of diagnosis impressions and tissular vestiges. The fragment, which has a half-cylindrical shape and a concavity along the longitudinal axis, is devoid of primary xylem and reveals a secondary xylem with few defined axial and radial systems. The anatomic characteristics of the secondary wood body indicate taxonomic affinity of the fossil wood with the most representative genus in the assemblage, increasing the establishing of relationships between the pith casts and the gondwanic taxa describe until the present, and suggest that the occurrence of these pith casts in the gondwanic sediments is probably because of environmental influences.